Targeting to brain tumor: Nanocarrier-based drug delivery platforms, opportunities, and challenges - Ladi Alik Kumar; Gurudutta Pattnaik; Bhabani Sankar Satapathy; S Swapna; Dibyalochan Mohanty (Journal of Pharmacy and Bioallied Sciences, 2021)
Cancer is a class of disorder characterized by anomalous growth of cells escalating in an uncontrolled way. Among all the cancers, treatment of cancerous brain tumors has been a tough challenge for the research scientists. Moreover, the absence of early-stage symptoms delays its diagnosis, consequently worsening its severity. Conventional treatments such as surgery, radiation, and chemotherapy are still linked with several limitations. The therapeutic effect of most of the anticancer drugs is highly restricted by their inability to pass the blood–brain barrier, low solubility, limited therapeutic window, and so on. Alarming incidences of brain cases associated with low survival rate across the globe coupled with the inefficiency of current treatment strategies have forced the formulation scientists to investigate nanotechnology-based advanced therapeutic approaches to tackle the disease. Various nanoplatforms such as polymeric nanoparticles (NPs), nanoliposomes, dendrimers, carbon nanotubes, and magnetic NPs have been reported in the past years to improve the drug administration into brain tumor cells and to minimize their off-target distribution for lesser side effects and better treatment outcomes. The review presents updated information on the nanocarrier-based drug delivery systems reported in the past few years for the treatment of brain tumor along with new advancements in this field. It also throws some light on the recent challenges faced in the practical field for the successful clinical translation of such nanodrug carriers along with a discussion on the future prospects.